A Systematic Literature Review On The Protection And Promotion Of Human Rights In Indonesia - Ulul Albab; Stanny Terianus Rumaseb; Sarwani Sarwani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Pancasila, as Indonesia’s foundational ideology, plays a central role in guiding the nation’s democratic governance and shaping its human rights framework. Despite its normative strength and universal values, the implementation of Pancasila in protecting human rights remains challenged by selective interpretations, legal inconsistencies, and socio-political dynamics that often limit its transformative potential. This study employs a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines, systematically analyzing peer-reviewed Scopus-indexed publications from 2014–2025. The methodology integrates qualitative thematic synthesis and bibliometric mapping using VOSviewer, combining network, overlay, and density visualizations to capture both substantive content and the intellectual structure of the literature. The review identifies four major thematic dimensions: (1) humanity and social justice as core ethical values of Pancasila; (2) legal framework and reforms that seek to harmonize national laws with constitutional and international human rights principles; (3) challenges and critiques highlighting issues such as weak law enforcement, political intervention, and ideological contestation; and (4) educational and societal impacts, particularly the role of civic education and community-based initiatives in fostering rights awareness. Findings highlight that while Pancasila provides a robust ethical and legal foundation for human rights protection, its practical impact remains constrained by structural weaknesses, limited civic engagement, and inconsistent judicial practices. Bibliometric mapping reveals a growing scholarly interest in the areas of legal modernization, democratic governance, and the integration of human rights education within both formal and informal learning systems. This suggests that contemporary discourse is increasingly oriented toward reform and institutional strengthening. The study concludes that a synergistic application of Pancasila principles, comprehensive legal reform, and active civic participation is crucial for advancing human rights in Indonesia. Strengthening judicial independence, promoting inclusive legal frameworks, and enhancing civic education are key strategies to align Indonesia’s human rights practices with both its national values and international standards. Ultimately, this review contributes to scholarly discourse and policy development by providing a comprehensive synthesis of the intersection between ideology, democracy, and human rights in contemporary Indonesia.